2017
DOI: 10.1097/cmr.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics of early-stage melanoma patients: a cross-sectional study on 204 patients

Abstract: The presence of psychological distress has a negative impact not only on cancer patients' quality of life but also on the course of the disease, with slower recovery and increased morbidity. These issues are of particular importance in melanoma patients (MP), who remain at risk of disease progression for many years after diagnosis. This study aimed to investigate psychological distress, coping strategies, and their possible relationships with demographic-clinical features in patients with early-stage melanoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…(24)(25)(26)(27)(28)(29). The data obtained in our study are in accordance with the data obtained in other surveys that support the declining functioning of melanoma as well as the global quality of life as the symptomology grows (30)(31)(32).…”
Section: Discussionsupporting
confidence: 91%
“…(24)(25)(26)(27)(28)(29). The data obtained in our study are in accordance with the data obtained in other surveys that support the declining functioning of melanoma as well as the global quality of life as the symptomology grows (30)(31)(32).…”
Section: Discussionsupporting
confidence: 91%
“…[ 13 ] Some studies have shown that positive coping style is the protective factor of psychological stress, [ 14 , 15 ] and negative coping is related to psychological stress such as anxiety and depression. [ 16 ] Besides, self-efficacy played a partial intermediary role between social support and positive coping style. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…There were publications on comorbidities in SC patients, HRQoL after treatment and many studies dedicated to different aspects of QoL in different populations of SC patients including studies on behaviour modification, predictors of QoL, predictors of survival, supportive care needs, coping strategies and fear of cancer recurrence…”
Section: Resultsmentioning
confidence: 99%